Tree‐Inspired Ultralong Hydroxyapatite Nanowires‐Based Multifunctional Aerogel with Vertically Aligned Channels for Continuous Flow Catalysis, Water Disinfection, and Solar Energy‐Driven Water Purification - Xiong, Zhi‐Chao; Zhu, Ying‐Jie; Wang, Zhong‐Yi; Chen, Yu‐Qiao; Yu, Han‐Ping (Advanced functional materials, 2022)
Water pollution and freshwater shortage have deteriorated the global water crisis. Developing sustainable methods to alleviate contaminated water has become an urgent affair. Herein, inspired by water transportation and transpiration of natural trees, the authors report an ultralong hydroxyapatite nanowires‐based biomimetic aerogel with vertically aligned channels and multiple functions for continuous flow catalysis, water disinfection, solar energy‐driven water purification, and seawater desalination. Ultralong hydroxyapatite nanowires act as carriers to immobilize catalyst nanoparticles and serve as building blocks to assemble with chitosan to form the biomimetic aerogel with structure‐function integration. Benefiting from the interconnected cellular structure, unidirectional aligned channels, nanowire‐interwoven networked pore wall, and evenly distributed catalyst nanoparticles, the biomimetic aerogel exhibits high catalytic activity (97.6% treatment efficiency) and permeability (1786 L m−2 h−1), excellent recyclability and stability in continuous flow catalytic degradation of methylene blue solely driven by gravity. The biomimetic aerogel exhibits excellent performance for bacteria removal and anti‐biofouling. The superior photothermal conversion and heat confinement properties enable the biomimetic aerogel with a high efficiency (86.7%) for solar energy‐driven seawater desalination and wastewater purification under one sun irradiation. The multifunctional biomimetic aerogel has promising applications in catalytic reactions, wastewater remediation, and environmental engineering. A tree‐inspired multifunctional aerogel with vertically aligned channels is fabricated from ultralong hydroxyapatite nanowires, immobilized palladium nanoparticles, and chitosan through a unidirectional freeze‐drying approach. The biomimetic aerogel exhibits high performances in gravity‐driven continuous flow catalytic reactions, water disinfection, and solar energy‐driven water purification and seawater desalination.